DEFINICJA POJĘCIA „DZIEŁO SZTUKI” I JEJ PRZYDATNOŚĆ W STOSUNKACH UBEZPIECZENIOWYCH - Górecki, Piotr (Zeszyty Prawnicze, 2016)
The article analyses the definition of “an item of fine art” and its practical application in the spectrum of insurance relationships. The definition is considered from a general point of view as well as from the legal perspective. It is also collated with synonymous concepts (i.e. antiquity, cultural property, exhibits) and briefly examined in different legal contexts (fiscal, administrative, international, civil). This review leads to a conclusion that it is impossible to find a satisfactory and generally applicable definition of “an item of fine art,” and that therefore searching for such a definition is a waste of time. On the other hand, attempts to define “an item of fine art” shed light on its classic features, which may be useful in certain cases. The article draws attention to the indirect impact of certain reflections and observations regarding “fine art,” notably their effect on the interpretation of the concept of “items of fine art” in civil law and civil contracts. It also shows that an accurate definition may be essential in an insurance relationship, since the subject of insurance protection has to be clearly defined. These practical implications apply particularly to situations when an item of fine art is not the sole object of insurance protection and when it is an element of an insured collection. The article considers not only the applicable legislation but also the general terms and conditions used by insurance companies.